A comprehensive review of biochar-derived dissolved matters in biochar application: Production, characteristics, and potential environmental effects and mechanisms. Issue 3 (June 2021) - Yang, Fang; Wang, Cuiping; Sun, Hongwen
Abstract: Biochar-derived dissolved organic matter (BDOM) is an important component released from biochar. BDOM's properties are directly dependent on the biochar resource, pyrolysis temperature, extraction method. BDOM plays a crucial role in controlling the interactions between pollutants and biochar and enhances the sorption sites of both organic and inorganic contaminants, which increases the mobility of pollutants in aquatic environments. In addition, BDOM can oxidize and reduce pollutants and even degrade some organic contaminants by electron transfer and free radicals. Moreover, the content and physicochemical properties of BDOM affected the behavior of soil organic matter. Interestingly, BDOM not only acts as an exogenous substance that is beneficial to certain microorganisms but also interacts with contaminants and bacteria by electron transfer, affecting bacterial abundance and transcription and even inducing the expression of genes. Moreover, the nutrient elements of BDOM are directly utilized by plants, and some components are involved in plant metabolism to defend against disease, and even contaminants. In particular, some compositions from BDOM can act as stimulants and hormone analogs of plants, and can directly promote plant growth through inducing the expression of certain genes. However, specific mechanisms, e.g., interactions among BDOM, contaminant, microorganisms, plant, remain somewhat unclear but still need be investigated to improve the remediation efficiency of Environ. Pollut. using biochar. Graphical Abstract: ga1 Highlights: Summarized the characterization techniques and affecting factors of biochar-derived dissolved organic matter performance. The role of biochar-derived dissolved organic matter in affecting pollutants. Review the existing knowledge on the effects of biochar-derived dissolved organic matter on soil microbes and plant growth. Suggested future research topics of biochar-derived dissolved organic matter from biochar application.